Wychowanie fizyczne na Uniwersytecie Notre Dame w South Bend Indiana – tradycja, proces, nauczyciele - Marciniak , Michał (Studia Edukacyjne, 2017)
The author of this article presensts the structure of physical education and sports at the academic level at Notre Dame University in South Bend Indiana. The first part describes the historical aspect, the most important dates, names of the university. The next part is an analysis of the program of physical education classes, sports facilities and budget for sport. In the last part, the author attempted to present a episode of his qualitative research at Notre Dame University during his stay in 20122014. The research concerned the professional satisfaction of physical education teachers at the University of Notre Dame.